EFEK MEDIASI KEPERCAYAAN DALAM POLA HUBUNGAN ANTARA KUALITAS PELAYANAN, CITRA PERUSAHAAN, WORD OF MOUTH, DAN MINAT NASABAH (Studi Pada Nasabah Bank Jateng Kantor Cabang Pembantu Simo Boyolali) - Siti Almaidah (STIE Atma Bhakti, 2019)
This study aims to examine the mediating effect of trust in the pattern of relationships between service quality, corporate image, word of mouth, and customer interest. The research design used was a survey design. The number of samples involved was 80 customers of DPLK Setia Bank in Central Java, Branch Office Simo Boyolali. The sampling technique uses purposive sampling with a limitation has been a customer for 1 to 5 years. Methods of data analysis using testing of research instruments, classical assumption tests, and hypothesis testing using path analysis. The results of this study there is a direct relationship between service quality, company image, word of mouth, and trust in customer interest, and there is an indirect relationship between service quality, company image, and word of mouth to customer interest through trust. Based on the results of this study, it is better for the Central Java Bank's Branch Office Simo Boyolali to be able to provide the best service, strengthen the company's positive image, and implementing effective marketing strategies through word of mouth. So that it increases trust and can attract customer interest.